Medieval Muslim scholars: teachers, missionaries and theoreticians, Qādi al-Nu'mān as a case study - Tahraoui, Ramdane; Merah, Souad (IIUM Press, 2017)
One distinct character of education in medieval Islam is the fact that teaching and learning activities were not regarded by both the shuyūkh (master scholars) and talaba or tullāb (students) as a waẓīfah (job) for the former and potential source of income after graduation for the latter. On the contrary, both segments took teaching and learning as a noble mission in life, which promised social veneration in this life and God’s reward in the other. Apart from the religious drive, the dedication and zeal of both, the shuyūkh and their tullāb was somtimes stimulated by sectarian motives. The truth is that in those ages, it was customary for Muslim states, whether from the Sunni mainstream or from the minority Shī’a to manage and supervise intellectual activities, including institutions of learning, curriculum, human capitals (scholars, and students) in a flexible way. For instance, intellectual life was not run by one particular office, although educational policies were largely politicized in the case of the Fatimids. Due to such dynamic intellectual ambiance, many prominent scholastic figures emerged during this period and played a crucial role in the dissemination of knowledge, religious propaganda and sectarian dogmatic debate. This paper highlights the role and the contribution of medieval scholars through the case of qādī al-Nu'mān, one of the most influential and notable medieval Ismā’īli scholars who served under the reign of the Fatimids. It also aims to analyze the complicated role of this scholar and his influence on the Intellectual life. The results of this study showed that al-Nu'mān devotedly served the Ismā’īli mazhab with the heart of a candid believer and the mind of a sholar. He used his intellect and pen to defend the Ismā’īlī cause on many fronts